Efficacy of different irrigation techniques on calcium hydroxide removal from the root canal - Opačić-Galić Vanja; Stašić Jovana N. (Serbian Medical Society - Dental Section, Belgrade, 2018)
Introduction Calcium hydroxide (CH) is a medicament widely used in endodontic treatment due to its antibacterial, regenerative and biocompatible properties. Studies have shown that remaining CH on root canal walls and dentinal tubules can compromise sealer penetration, leading to its weak adhesion, volume change and, consequently, apical leakage. The aim of this study was to compare the efficacy of four different techniques in removing calcium hydroxide from the root canal. Material and Methods 32 extracted single-rooted teeth with one canal were used in this study. The canals were prepared using BioRaCe system (FKG Dentaire, Swiss) BR5 40/.04 with sodium hypochlorite irrigation after each instrument. Longitudinal grooves were formed on the proximal root surfaces. All canals (except negative control) were filled with aqueous CH suspension. After seven days of incubation, the teeth were allocated into the four groups (n=7), plus positive and negative control. Four techniques (systems) for CH removal were tested: conventional syringe irrigation (CSI), passive ultrasonic irrigation (PUI), XP-endo Finisher (FKG Dentaire, Swiss) and Canal Brush (Roeko, Coltene) with irrigation of 5 ml 2% NaOCl and 5 ml 10% citric acid. All the roots were then split into the two halves with chisel and observed under the stereomicroscope (Boeco, Germany) at magnification of 20x. The area with remaining CH on the root canal wall surface was then divided with the total root canal surface area (%). The obtained results were statistically processed using One-way ANOVA and Tukey post-hoc test (p<0.05). Results The most efficient system was XP-endo Finisher with 91.33% of clean surface, followed by PUI 88.36%, Canal Brush 87.83%, and CSI with 66.92%. Conclusion None of the systems completely removed the traces of the medicament from the root canal. For optimal clinical success, it is necessary to combine various systems with copious irrigation.